Propensity to export and effects on cluster development: A comparative study of the Cyprus and Greek solar thermal clusters - Petrou, Andreas; Maxoulis, Christos N.; Haralambous, Harris (My University, 2008)
Access to sophisticated demand is critical for cluster upgrading in developing countries. Despite this, the role of exports in cluster development has not been adequately researched. This study tries to answer two questions; what are the factors that increase the propensity of a cluster to successfully engage in exports and how exports affect cluster upgrading. In order to isolate the effect of exports, two clusters are studied, the Cyprus and the Greek solar thermal clusters. Despite the fact that these two clusters emerged in similar environments, today they present some distinct differences which could be explained by the different levels of success in exporting. Our findings suggest that the export vision shared among cluster participants, and the collaboration to achieve the vision are of critical importance in penetrating sophisticated export markets. This study highlights the positive influence of exports on cluster development and provides managers and policy makers with an indication of which factors contribute to successful exporting.
Keywords: Cluster upgrading; Cyprus; Diamond mode; Exports; Greece; Solar thermal systems